Development of a system combining comprehensive genotyping and organoid cultures for identifying and testing genotype-oriented personalised medicine for pancreatobiliary cancers. (May 2021) - Shiihara, Masahiro; Ishikawa, Tomohiko; Saiki, Yuriko; Omori, Yuko; Hirose, Katsuya; Fukushige, Shinichi; Ikari, Naoki; Higuchi, Ryota; Yamamoto, Masakazu; Morikawa, Takanori; Nakagawa, Kei; Hayashi, Hiroki; et al.
Abstract: Background: Pancreatobiliary cancer is a highly aggressive tumour with a dismal prognosis. Personalised medicine represents a promising and effective therapeutic approach for this intractable disease. In this study, we aimed to establish a system for identifying and testing genotype-oriented targeted drugs for pancreatobiliary cancers by combining exome sequencing and organoid culture of primary tumours. Methods: Tumour cells isolated from resected tumours were subjected to organoid cultures based on published protocols with modifications. Exome sequencing was performed on the primary tumours. Histopathological and molecular features of the primary tumours were validated in the corresponding organoids. Genotype-oriented candidate targeted drugs were identified from exome sequencing, and their efficacies were tested in the organoids. Results: Organoid cultures succeeded in 30 of 54 (55.6%) cases. Six primary cancers of the biliary tract and gall bladder were subjected to exome sequencing, which revealed a variety of somatic mutations of genes involved in signalling pathways, epigenetic modifiers, genome maintenance and metabolic enzymes. Most of the organoids of these 6 cases showed identical histopathological features and genomic aberrations as those of the primary tumours. Some of the aberrations were candidates for targeted therapies. Integrin-linked kinase (ILK ) was one such candidate target, and an ILK inhibitor was confirmed to suppress proliferation of patient-derived organoids. Conclusions: By combining exome sequencing and organoid culture, our model enabled to identify genotype-oriented targets for personalised medicine and to test efficacies of candidate targeted drugs in the organoids. The current proof-of-concept approach could increase therapeutic opportunities for patients with pancreatobiliary cancers. Graphical abstract: Image 1 Highlights: Organoids were obtained from 29 of 54 (53.7%) pancreatobiliary cancers. Most of the organoids retained genotypes and histological phenotypes of primary tumours. Exome sequencing unveiled diverse mutations in primary biliary tumours. Organoids served for testing genotype-oriented targeted drug candidates.